Unpacking the dynamics of collegial networks in relation to beginning teachers' job attitudes. Issue 5 (3rd September 2021) - Thomas, Laura; Rienties, Bart; Tuytens, Melissa; Devos, Geert; Kelchtermans, Geert; Vanderlinde, Ruben
ABSTRACT: Previous research has pointed at the pivotal role of professional collegial support relationships to keep beginning teachers in the profession. In this study, we build on previous research by using follow-up mixed-method social network data to explore (1) to what extent, in what ways and for which reasons beginning teachers' work-related network (position) changes throughout a school year, and (2) how the network (position) of beginning teachers influences their job attitudes, as important precursors of teacher retention. Five follow-up case-studies of beginning teachers and their school teams were explored. The network data showed that some teachers had a central and stable position in their team, while others were more peripheral and showed considerable changes in their work-related relations. The interviews with the beginning teachers revealed several reasons for the formation, loss and retention of their work-related ties, such as physical proximity, network intentionality and the presence of a staffroom. Finally, the results indicated that the professional support in these work-related ties can play an important role in beginning teachers' job attitudes, or can act as a mitigating factor in case of experienced challenges. In this respect, the structural and cultural conditions needed for teachers to professionally connect require our attention.